Elementary School Education Promotion Techniques Via Social Media - Sahrawi, Saimima; Mai Dhuhani, Elfridawati; Anasufi, Banawi (Journal of Education Technology and Inovation, 2025)
Online-based education in its current application provides opportunities for people to always follow the development of the world of education. The purpose of this information disclosure is so that the public can find out about the educational programs that are carried out in each school in real time. This process certainly requires an effective promotion strategy to introduce the existence and quality of educational institutions to the wider community. Therefore, this paper aims to examine the promotion strategy carried out by an educational institution. This study uses a qualitative method with data collection techniques through interviews and observations. The focus of the research is directed to find out the promotional strategies carried out by SD Islam Al Bina Masohi in Maluku, both online and offline. The results of the study showed that SD Islam Al Bina Masohi implemented various promotional strategies, including by utilizing social media such as Facebook and WhatsApp groups to publish school programs and activities. Moreover, Schools also place human resources (HR) or educators who have superior competencies to interact with students' parents, especially in routine recitation activities and the provision of quality educational services. These strategies are an important part of building a positive image and public trust in these educational institutions